2016
DOI: 10.1111/ane.12561
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis sequelae at long-term follow-up: a self-reported case-control study

Abstract: At the long-term follow-up, the patients scored significantly lower in a diversity of neurocognitive and motor symptoms, in comparison with controls. These sequelae and their pathogenesis should be further explored and specific neurocognitive assessment tests are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 15 publications
1
37
0
1
Order By: Relevance
“…Mental fatigue is a common symptom following traumatic brain injury (TBI) (Cantor, Gordon, & Gumber, 2013), stroke (Staub & Bogousslavsky, 2001), meningitis or encephalitis (Veje et al., 2016), and neurological diseases (Penner & Paul, 2017). In the case of long‐lasting mental fatigue, even once a person has recovered, they still may have difficulty returning to work and pursuing social activities.…”
Section: Introductionmentioning
confidence: 99%
“…Mental fatigue is a common symptom following traumatic brain injury (TBI) (Cantor, Gordon, & Gumber, 2013), stroke (Staub & Bogousslavsky, 2001), meningitis or encephalitis (Veje et al., 2016), and neurological diseases (Penner & Paul, 2017). In the case of long‐lasting mental fatigue, even once a person has recovered, they still may have difficulty returning to work and pursuing social activities.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological sequelae is reported in 30-40% of cases, ranging from concentration disabilities to tremor and paresis. [1,[6][7][8][9][10][11][12] In Europe two inactivated vaccines are presently registered, FSME-immune (available in Sweden since 1980s, Pfizer) and Encepur (GSK). The immunogenicity of any of those vaccines is 95-100%.…”
Section: Tbe Infection and Preventionmentioning
confidence: 99%
“…The probabilities of events after the incidence year were derived from several follow-up studies on TBE-infection. [1,[6][7][8][9][10][11][12]…”
Section: Tbe Incidence and Long Term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three known subtypes, the Siberian and Far-Eastern subtypes are associated with comparatively more severe disease than the European subtype [13]. Clinical manifestations range from fever, headache and nausea to encephalitis with or without altered consciousness [14]. One study of the Polish health registry reported that TBE presents as meningitis in about 50 % patients, meningoencephalitis in about 40 % and meningoencephalomyelitis in about 10 % [13].…”
Section: Tick-borne Encephalitis Virusmentioning
confidence: 99%